Myocardial perfusion imaging using technetium-99m sestamibi in asymptomatic diabetic patients - Mohagheghie, A.; Ahmadabadi, M. N.; Hedayat, D. K.; Pourbehi, M. R.; Assadi, M. (Nuklearmedizin - NuclearMedicine, 2011)
Myocardial perfusion single-photon emission computed tomography (SPECT) has been extensively applied in the clinical assessment of patients with diabetes mellitus. The aim of the present study was to evaluate stress technetium- 99m sestamibi SPECT MPI perfusion in silent myocardial ischemia and its association with some clinical and laboratory parameters in an asymptomatic diabetic population. Patients, material, methods: 83 subjects (age: 57.1 ± 6.9 years) with at least five years history of type 2 diabetes, and no suspected or documented coronary artery disease (CAD) accomplished myocardial perfusion imaging; angiography was also performed in patients with abnormal MPI. Results: MPI results showed that 58 patients had normal myocardial perfusion, while 25 patients showed perfusion defects (23 reversible and 2 fixed) on MPI. 12 out of the 25 (48%) with abnormal MPI findings represented abnormal angiography. We observed that pretest likelihood of CAD (odds ratio 2.32; 95%-CI: 1.05–5.13; p = 0.038) and higher HbA1c level (odds ratio 1.70; 95%-CI, 1.07–2.71; p = 0.02) were independently associated with abnormal MPI. Conclusion: Occult CAD was present on MPI in 1/3 patients with DM without abnormal electro cardiographic findings or evidence of peripheral arterial disease.
Keywords: Myocardial perfusion imaging; asymptomatic diabetic patients; silent ischaemia; coronary artery disease; haemoglobin A1c